EXPLORING STUDENTS’ MISCONCEPTIONS OF FUNGI USING FOUR TIER DIAGNOSTIC TEST - Utari, Fitriana Dwi; Maridi, Maridi; Ramli, Murni (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Students’ misconceptions still become major focus of educational research in recent years. Information on students’ conceptual understanding and students’ misconceptions is necessary so that the teachers can detect misconception experienced by students. This study evaluated students’ conceptual understanding and misconceptions about Fungi using four tier diagnostic tests. Results showed that students' understanding was considered as poor. Misconceptions rates were also high with misconceptions about characteristics, reproduction, growth factor, classification, and Fungi role in life as misconceptions commonly found in the students.